Giant Morel-Lavallée lesion complicated with open pelvic fracture: a rare case report - Li, Xiaomin; Li, Rui; Luo, Xiangli; Chen, Teng; Wu, Jian (Frontiers in Surgery, 2025)
BackgroundMorel-Lavallée lesion (MLL) is a rare closed degloving injury from high-energy shear/crush trauma, often linked to pelvic/acetabular fractures. Due to limited clinical awareness, it is highly prone to misdiagnosis, potentially causing severe complications like infection and skin necrosis. Existing literature rarely documents giant MLL with open pelvic fractures. This article reports such a case in an obese patient after heavy-object impact, aiming to enhance understanding and improve management of complex injuries.Case presentationA 27-year-old male sustained lumbosacral giant MLL and open pelvic fracture from workplace heavy-object crush. The MLL was unrecognized for two weeks at another hospital. Upon transfer, he had hemorrhagic shock, fluctuating lumbosacral swelling, and localized skin necrosis. Imaging showed comminuted left iliac fracture with extensive soft tissue edema and gas.ManagementA three-stage surgery was used. Stage 1: muscle debridement, fracture fixation, and vacuum-assisted closure (VAC) to address acute injury and control infection. Stage 2: debridement, antibiotic-loaded bone cement implantation, and continued VAC for osteomyelitis treatment and bone healing. Stage 3: flap reconstruction and skin grafting to restore soft tissue integrity.OutcomeThe patient was discharged one month postoperatively with viable skin grafts. At 3-month follow-up, fracture and wound healed well, confirming the staged approach's effectiveness.ConclusionMLL is often overlooked in high-energy trauma, emphasizing early comprehensive exams plus imaging to avoid misdiagnosis. For MLL with fractures, staged treatment is advisable: early radical debridement and VAC to control infection, followed by fixation and soft tissue reconstruction when stable. VAC reduces infection risk by minimizing exudation and promoting granulation. Obese patients, with loose adipose compartments, face higher MLL risk and need special attention. Future research should explore minimally invasive techniques to optimize outcomes.